STRENGTHENING NATIONAL CHARACTER BY RECONCILIATION THE TESTAMENT: LOCAL LITERATURE IN THE POST-NATIONAL ERA - Nahdi, Khirjan; Yunitasari, Dukha; Suhartiwi, Suhartiwi; Atiaturahmaniah, Atiaturahmaniah; Ibrahim, Doni Septu Marsa (VELES Voices of English Language Education Society, 2020)
This study aims to find the value of nationality in Hamzanwadi's testament. Hamzanwadi is a local figure in Lombok with   global outlook. Testament in the form of rhymes and poetry contain national values, need to be strengthened in the post-national era. The testament understood through the dialectical and hermeneutic methods. Through dialectics and hermeneutics, it is understood that the value of Indonesian nationality regarding Pancasila, the 1945 Constitution, the Republic of Indonesia, and Unity in Diversity. National presence of the four national values is illustrated through the birth of religiousism, faith, piety, justice and prosperity. The results of the discussion focused on the nationality recommended of the post-national era through the transfer of knowledge, strengthening of values, value implementation by all parties and all institutions.